Özden Selenge'nin Romanlarında Arzu Mekanizmasının Evrenselliği - Hurol, Yonca (EMU, 2001)
Özet Bu calışmanın amacı Kıbrıslı kadın yazar ve ressam Özden Selenge'nin romanlarındaki arzu mekanizmasının evrensel niteliklerinin tartışılmasıdır. Bu amaçla özel olarak Selenge'nin anlaşılmasına uygun bir izlek tayin edilmiş ve Selenge, bir okuyucusu olan bu çalışmanın yazarında uyandırdığı, arzu mekanizmasi üzerinden anlaşılmaya calışılmıştır. Çünkü, bu çalışmada benimsenen bakış açısına göre bir sanat eserinin ve özellikle de bir sanat eserindeki arzu mekanizmasının tarafsız bir bakış açısı ile değerlendirilmesi mümkün değildir. Selenge'deki arzu mekanizmasının evrenselliğini tartışabilmek amacı ile oluşturulan bu izlek, öncelikle Selenge'nin romanlarındaki arzu mekanizmasının evrensel ve yerel çekiniklik (minority) ile ilişkisinin, daha sonra ise evrensel çekinik özelliklerin yerel olanlar üzerindeki hakimiyeti sonucunun kesinlestirilmesi amacı ile ayni arzu mekanizmasının biçimsel özellikler ile olan ilişkisinin incelenmesinden oluşmaktadır. Abstract Universality of the Desire Mechanism (32) in Ozden Selenge's Novels This paper is about the significance of the desire mechanism in the novels of Ozden Selenge who is a Cypriot woman writer and artist. For this purpose, a specific process is applied in order to understand Selenge's novels. According to this process, desire mechanism is perceived self-reflectively as it affects the writer of this paper. According to this perspective, it is not possible to make an objective evaluation of an art product and especially the desire mechanism in it. The first two parts of the paper are about the universal and local characteristics that are presented in these novels. It is shown that impossibility of love forms an universal desire mechanism in both of Selenge's two novels, while the main desire mechanism of her last novel is the possibility of friendship. It is also shown that the way Selenge understands love and friendship corresponds to a certain perspective of women. However, this is such a woman point of view that does not have any feminine (a tendency to imitate), feminist (a tendency to oppose) or female (a tendency to be passive) characteristics. It is a point of view that is infinitely open to in-between categories in order to produce an extremely fine particularity. The target of the paper is to explore whether these universal characteristics are dominant on the local ones. Selenge produces these universal desire mechanisms by giving the local desire mechanisms to the service of the universal ones. Repression applied by the specific (well known) social problems is inverted with the help of the particularity of her peaceful characters. This is the way she highlights the local social problems, while achieving the universality at the same time. The last part of the paper contains an evaluation to discover if there is any consistency between the formal characteristics of the novels and the domination relationship between universal and local characteristics in them. The form is not dominant in Selenge's novels. However, it series the purpose of producing a universal desire mechanism with the help of local ones. The main formal characteristics of her novels are achieved with the help of the tension between the use of time and accent differences of the characters. Identity categories of the local characters are defined with the help of their accents. However, by turning back to their personal and family histories in a free form and by telling specific events, these categories change to become peaceful particularities. At this stage, the only remaining characteristic from the categories is the differences between their accents. In this way the rise of universal desire mechanisms ore made possible. Problems between the identity categories are eliminated and the strengths of accents against repression are freed. The use of local desire mechanisms in the service of universal ones also distinguishes Selenge's writing from Western literature that depends on the relationship between universality and form.
Bu çalışmada Özden Selenge'nin romanlarındaki arzu mekanizmaları Deleuze ve Guattari'nin post-yapısalcı bakış açısından incelenmektedir.
Keywords: Arzu mekanizması, roman, Özden Selenge, Deleuze & Guattari